Circulating monocytes and tumor-associated macrophages express recombined immunoglobulins in glioblastoma patients - Busch, Svenja; Talamini, Marina; Brenner, Steffen; Abdulazim, Amr Nabil; Hänggi, Daniel; Neumaier, Michael; Seiz-Rosenhagen, Marcel; Fuchs, Tina (Clinical and translational medicine, 2019)
Glioblastoma is the most common and malignant brain tumor in adults. Glioblastoma is usually fatal 12-15 months after diagnosis and the current possibilities in therapy are mostly only palliative. Therefore, new forms of diagnosis and therapy are urgently needed. Since tumor-associated macrophages are key players in tumor progression and survival there is large potential in investigating their immunological characteristics in glioblastoma patients. Recent evidence shows the expression of variable immunoglobulins and TCRαβ in subpopulations of monocytes, in vitro polarized macrophages and macrophages in the tumor microenvironment. We set out to investigate the immunoglobulin sequences of circulating monocytes and tumor-associated macrophages from glioblastoma patients to evaluate their potential as novel diagnostic or therapeutic targets.
Gesehen am 01.10.2019